SPECIFIC HANDBALL GAME MEANS' OPTIMIZATION TO FULFILL PHYSICAL EDUCATION AND SPORT'S OBJECTIVES IN THE 7TH GRADE - Marcel Constantin NICOLAEVICI; Leuciuc Florin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
Due to the insufficient time granted to physical education in education planning, the 100 minutes of weekly cycle for a student with no skills or concerns, allowing to a small extend to fulfill some physiological and psychomotor effects really helpful for students throughout school and then, throughout life. Another reason to justify choosing this subject is the attempt to capitalize the entire potential of time had in school and out of school activity, enhancing motor potential of students and the material conditions the school has, with the goal of realizing a healthy education to accomplish physical education objectives. This activity helps to fulfill physical education objectives by high parameters of physical and motor development, framing various basic and specific skills, framing skills of independent practice of physical exercises, seeking in knowledge about game setup and rules.